Facile Synthesis and Characterization of Palm CNF-ZnO Nanocomposites with Antibacterial and Reinforcing Properties - Supramaniam, Janarthanan (Int J Mol Sci, 2021)
Cellulose nanofibers (CNF) isolated from plant biomass have attracted considerable interests in polymer engineering. The limitations associated with CNF-based nanocomposites are often linked to the time-consuming preparation methods and lack of desired surface functionalities. Herein, we demonstrate the feasibility of preparing a multifunctional CNF-zinc oxide (CNF-ZnO) nanocomposite with dual antibacterial and reinforcing properties via a facile and efficient ultrasound route. We characterized and examined the antibacterial and mechanical reinforcement performances of our ultrasonically induced nanocomposite. Based on our electron microscopy analyses, the ZnO deposited onto the nanofibrous network had a flake-like morphology with particle sizes ranging between 21 to 34 nm. pH levels between 8–10 led to the formation of ultrafine ZnO particles with a uniform size distribution. The resultant CNF-ZnO composite showed improved thermal stability compared to pure CNF. The composite showed potent inhibitory activities against Gram-positive (methicillin-resistant Staphylococcus aureus (MRSA)) and Gram-negative Salmonella typhi (S. typhi) bacteria. A CNF-ZnO-reinforced natural rubber (NR/CNF-ZnO) composite film, which was produced via latex mixing and casting methods, exhibited up to 42% improvement in tensile strength compared with the neat NR. The findings of this study suggest that ultrasonically-synthesized palm CNF-ZnO nanocomposites could find potential applications in the biomedical field and in the development of high strength rubber composites.